Clinical but Not Histological Outcomes in Males With 45,X/46,XY Mosaicism Vary Depending on Reason for Diagnosis - GÜRAN, TÜLAY (ENDOCRINE SOC, 2019)
Context: Larger studies on outcomes in males with 45,X/46,XY mosaicism are rare. Objective: To compare health outcomes in males with 45,X/46,XY diagnosed as a result of either genital abnormalities at birth or nongenital reasons later in life. Design: A retrospective, multicenter study. Setting: Sixteen tertiary centers. Patients or Other Participants: Sixty-three males older than 13 years with 45,X/46,XY mosaicism. Main Outcome Measures: Health outcomes, such as genital phenotype, gonadal function, growth, comorbidities, fertility, and gonadal histology, including risk of neoplasia. Results: Thirty-five patients were in the genital group and 28 in the nongenital. Eighty percent of all patients experienced spontaneous pubertal onset, significantly more in the nongenital group (P = 0.023). Patients were significantly shorter in the genital group with median adult heights of 156.7 cm and 164.5 cm, respectively (P = 0.016). Twenty-seven percent of patients received recombinant human GH. Forty-four patients had gonadal histology evaluated. Germ cells were detected in 42%. Neoplasia in situ was found in five patients. Twenty-five percent had focal spermatogenesis, and another 25.0% had arrested spermatogenesis. Fourteen out of 17 (82%) with semen analyses were azoospermic; three had motile sperm. Conclusion: Patients diagnosed as a result of genital abnormalities have poorer health outcomes than those diagnosed as a result of nongenital reasons. Most patients, however, have relatively good endocrine gonadal function, but most are also short statured. Patients have a risk of gonadal neoplasia, and most are azoospermic, but almost one-half of patients has germ cells present histologically and up to one-quarter has focal spermatogenesis, providing hope for fertility treatment options.
Keywords: IN-VITRO PRODUCTION; GONADAL-DYSGENESIS; TURNER-SYNDROME; GONADOBLASTOMA; MANAGEMENT; PHENOTYPE; KARYOTYPE; CHILDREN; CELLS; ASSOCIATIONS